Fluted projectile points in a stratified context at the Raven Bluff site document a late arrival of Paleoindian technology in northwest Alaska. Issue 1 (24th September 2018) - Buvit, Ian; Rasic, Jeffrey T.; Kuehn, Steven R.; Hedman, William H.
Abstract: Our understanding of the northern fluted point tradition, a critical early New World lithic assemblage, is constrained by limited data from stratified, datable contexts. Here, we report on the Raven Bluff site in northwest Alaska, where fluted projectile points, microblades, and a well‐preserved faunal assemblage have been recovered from datable sediments. Results show that prehistoric inhabitants occupied a stone‐sorted polygon where retooling, game processing, and raw material procurement occurred mostly between 12, 720 and at least 11, 340 cal. yr B.P. We argue that once polygon formation ended, the stratigraphic context remained relatively intact. Further studies focused on the site's lithic and bone assemblages will help shape our understanding of the relationship between fluted point technology, microblades, and caribou hunting in northern Alaska.